2005
DOI: 10.1063/1.2055529
|View full text |Cite
|
Sign up to set email alerts
|

On the normalized turbulent energy dissipation rate

Abstract: This paper revisits values of the normalized energy dissipation rate (Cϵ) in different flows (two-dimensional wakes, grid turbulence, and homogeneous shear flow). Previously published as well as new data are considered over a relatively wide range of the Taylor-microscale Reynolds number Rλ. Cϵ exhibits wide scatter (in the range 0.5–2.5 for Rλ>50) although, for a given flow and initial conditions, it is independent of Rλ when the latter is sufficiently large. An alternative definition [B. R. Pearson, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
70
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 20 publications
10
70
0
Order By: Relevance
“…Based on Kolmorogov's dimensional scaling analysis assuming local isotropic turbulence in a flow field, energy dissipation rate ε can be computed as A more generic trend was observed by Burattini et al, (2005) by analysing different types of turbulent flow (both forced and decay) which suggested that this value remains approximately constant at ~ 0.5 when Re λ > 200. In the present study, A was assumed to be equal to unity due to similarity in the flow system with the work of Yang and Shy (2003) and no correction factor due to change in Re λ was used.…”
Section: Comparison Of Specific Energy Dissipation Rate Valuesmentioning
confidence: 97%
“…Based on Kolmorogov's dimensional scaling analysis assuming local isotropic turbulence in a flow field, energy dissipation rate ε can be computed as A more generic trend was observed by Burattini et al, (2005) by analysing different types of turbulent flow (both forced and decay) which suggested that this value remains approximately constant at ~ 0.5 when Re λ > 200. In the present study, A was assumed to be equal to unity due to similarity in the flow system with the work of Yang and Shy (2003) and no correction factor due to change in Re λ was used.…”
Section: Comparison Of Specific Energy Dissipation Rate Valuesmentioning
confidence: 97%
“…While the magnitude of the constant C ε , based on several experiments that were summarized in [57] and on the data obtained in [58], exhibits a relatively large scatter in the range of Reynolds numbers Re λ < 50, on the average the value of the constant C ε is closed to 1. Here Re λ is the Reynolds number based on the Taylor microscale.…”
Section: Production and Dissipation In Turbulent Convectionmentioning
confidence: 99%
“…This has been done in various studies over the last decades for homogeneous isotropic turbulence (HIT). Experimentally, the focus of attention was on grid-induced turbulence [8][9][10][11][12][13][14][15], whereas in numerical simulations periodic boundary conditions were used [16][17][18][19]. To what degree the decay of the turbulence depends on the initial conditions [20][21][22] and whether or not it is selfsimilar has controversially been debated [5,11,16,[23][24][25][26][27].…”
mentioning
confidence: 99%